2017
DOI: 10.5812/ircmj.58027
|View full text |Cite
|
Sign up to set email alerts
|

TP53 Codon 72 Genetic Polymorphism, rs1042522, Modifies the Association Between Tobacco Smoking and Breast Cancer Risk

Abstract: Background: TP53 tumor suppressor gene participates in several pathways involving in carcinogenesis such as cell cycle control, DNA repair, and apoptosis. A common TP53 SNP (guanine/cytosine nucleotide substitution at codon 72), rs1042522, affects the function of p53 protein and may influence tumor behavior in response to environmental carcinogens. Objectives: This study investigates the association between TP53 codon 72 polymorphisms, tobacco smoking, and breast cancer risk in southern Iranian women from Bush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The study by Khan et al, (2015) of Proline allele in the TP53 gene, Arg72Pro polymorphism in a Kashmir population, showed that no statistical difference was observed between patients and the control group in the TP53 gene, Arg72Pro polymorphism. Moradinasab et al, (2017) showed no major connection between breast cancer and codon 72 polymorphism in TP53. Fang et al, (2020) found that there was no important link between TP53 gene polymorphism and neuroblastoma susceptibility.…”
Section: Discissionmentioning
confidence: 87%
“…The study by Khan et al, (2015) of Proline allele in the TP53 gene, Arg72Pro polymorphism in a Kashmir population, showed that no statistical difference was observed between patients and the control group in the TP53 gene, Arg72Pro polymorphism. Moradinasab et al, (2017) showed no major connection between breast cancer and codon 72 polymorphism in TP53. Fang et al, (2020) found that there was no important link between TP53 gene polymorphism and neuroblastoma susceptibility.…”
Section: Discissionmentioning
confidence: 87%